2019
DOI: 10.1371/journal.pone.0216569
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of pulmonary caspases: Is this the key to Ureaplasma-driven chronic inflammation?

Abstract: Although accepted agents in chorioamnionitis and preterm birth, the role of Ureaplasma species (spp.) in inflammation-driven morbidities of prematurity, including the development of bronchopulmonary dysplasia, remains controversial. To add to scarce in vitro data addressing the pro-inflammatory capacity of Ureaplasma spp., pulmonary epithelial-like A549 cells and human pulmonary microvascular endothelial cells (HPMEC) were incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Previous studies on Ureaplasma spp. showed similar results; Wolfs et al showed there was no induction of apoptosis in enterocytes, while Silwedel et al reported endothelial cells (Wolfs et al 2013, Silwedel et al 2019. Several intracellular bacteria inhibit host cell apoptosis so they can persistently colonize the cells, which can facilitate their dissemination (Behar & Briken 2019, FitzGerald et al 2020.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on Ureaplasma spp. showed similar results; Wolfs et al showed there was no induction of apoptosis in enterocytes, while Silwedel et al reported endothelial cells (Wolfs et al 2013, Silwedel et al 2019. Several intracellular bacteria inhibit host cell apoptosis so they can persistently colonize the cells, which can facilitate their dissemination (Behar & Briken 2019, FitzGerald et al 2020.…”
Section: Discussionmentioning
confidence: 94%
“…Increased oxidative stress plays a key role in the progression of the inflammatory process. It has been shown that lung cells release these cytokines in response to oxidative stress 24,44 . Our study has demonstrated that pups in the control and APO groups had lower mean levels of TNF‐α, IL‐1β in lung tissue along with fewer alveolar macrophages than the pups in the BPD group.…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown that lung cells release these cytokines in response to oxidative stress. 24,44 Our study has demonstrated that pups in the control and APO groups had lower mean levels of TNF-α, IL-1β in lung tissue along with fewer alveolar macrophages than the pups in the BPD group. More importantly, we have observed that mean levels of TNF-α, IL-1β in lung tissue, and the mean alveolar macrophage score significantly decreased in the rats after APO treatment (Figures 4 and 7).…”
Section: F I G U R E 2 the Bpd Group Demonstrating Thickness Of Alveo...mentioning
confidence: 72%
“…infections in pulmonary epithelial cells led to the downregulation of caspase mRNA, suppressing apoptosis, and showed limited cytokine response. 56 Another study on Ureaplasma diversum infection in Hep-2 cells revealed a lower number of apoptotic cells and decreased expression of pro-apoptotic genes compared to uninfected control. 57 Interestingly, a recent study demonstrated that a novel virulence factor from Ureaplasma (UpVF) triggered endoplasmic reticulum stress but suppressed the apoptotic cascade in HeLa cells, leading to increased resistance to anticancer treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Ureaplasma spp. infections in pulmonary epithelial cells led to the downregulation of caspase mRNA, suppressing apoptosis, and showed limited cytokine response 56 . Another study on Ureaplasma diversum infection in Hep‐2 cells revealed a lower number of apoptotic cells and decreased expression of pro‐apoptotic genes compared to uninfected control 57 .…”
Section: Discussionmentioning
confidence: 99%